Global 16S rRNA diversity of provannid snail endosymbionts from Indo‐Pacific deep‐sea hydrothermal vents. Issue 2 (15th February 2022) - Breusing, Corinna; Castel, Jade; Yang, Yi; Broquet, Thomas; Sun, Jin; Jollivet, Didier; Qian, Pei‐Yuan; Beinart, Roxanne A.
Summary: Symbioses between invertebrate animals and chemosynthetic bacteria build the foundation of deep‐sea hydrothermal ecosystems worldwide. Despite the importance of these symbioses for ecosystem functioning, the diversity of symbionts within and between host organisms and geographic regions is still poorly understood. In this study we used 16S rRNA amplicon sequencing to determine the diversity of gill endosymbionts in provannid snails of the genera Alviniconcha and Ifremeria, which are key species at deep‐sea hydrothermal vents in the Indo‐Pacific Ocean. Our analysis of 761 snail samples across the distributional range of these species confirms previous findings that symbiont lineages are strongly partitioned by host species and broad‐scale geography. Less structuring was observed within geographic regions, probably due to insufficient strain resolution of the 16S rRNA gene. Symbiont richness in individual hosts appeared to be unrelated to host size, suggesting that provannid snails might acquire their symbionts only during a permissive time window in early developmental stages in contrast to other vent molluscs that obtain their symbionts throughout their lifetime. Despite the extent of our dataset, symbiont accumulation curves did not reach saturation, highlighting the need for increased sampling efforts to uncover the full diversity of symbionts within these and other hydrothermal vent species.